Considerations concerning CAVAT: what does its "tree amenity value" actually measure?. Issue 1 (2nd January 2020) - Price, Colin
ABSTRACT: CAVAT's system for amenity tree valuation is based on planting cost, modified by size and several physical and aesthetic factors. It does not represent actual replacement cost. Its adaptation for aesthetic valuation is contentious, partly because of arguable subjective judgements. The supposed mental frame of valuers causes serious miscalculation of unit value, because installation cost is divided by current basal area, not predicted lifetime basal area. Deriving an "annual unit value" offers a way to circumvent this problem. Which basket of services is valued is unclear. The value offers a possible starting point in negotiating compensation, but not "a market price" for amenity trees. While some problems are endemic to expert valuations, others are specific to this system. Identifying them might help in revising the system, to provide a value both rational and reasonable.